PENGGUNAAN METODE DISKUSI DAN MEDIA GAMBAR DALAM PEMBELAJARAN TENTANG KEDUDUKAN DAN PERAN ANGGOTA KELUARGA UNTUK MENINGKATKAN HASIL BELAJAR IPS KELAS II PADA SD NEGERI 35 PINCURAN VII - ASMIWATI ASMIWATI (STKIP Pesisir Selatan, 2019)
Social Sciences subject is one of the main subjects given at all levels of the school because it is related to daily life. This condition also occurs in grade II students of SDN 35 Pincuran VII, Tanah Datar Regency, with 21 students still lacking social sense. In this case students need to be confronted with real (concrete) reality. From the observations of the improvement of Social Science learning material